2012
DOI: 10.1021/ic300859n
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhydrides of (Ca,Sr,Ba)TiO3 Perovskite Solid Solutions

Abstract: The oxyhydride solid solutions (Ca,Sr)TiO(3-x)H(x) and (Sr,Ba)TiO(3-x)H(x) have been prepared by reducing the corresponding ATiO(3) oxides with calcium hydride. Under the reaction conditions examined, a hydride content of x = 0.1-0.3 was obtained for all compositions. Compared to our previous result with BaTiO(3-x)H(x), the larger particle size in this study (20-30 μm vs 170 nm) resulted in a somewhat lower hydride amount despite prolonged reaction times. We examined changes in cell volume, octahedral tilt ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 23 publications
13
113
2
Order By: Relevance
“…Further, at its peak, this leak rate exceeded that of the next largest point source in the United States-an underground coal mine in Alabama-by over a factor of 2 (14) and was a factor of 10 larger than the CH 4 leak rate reported from the Total Elgin rig blowout in the North Sea in 2012 (17). The Aliso Canyon CH 4 leak rates were comparable to the total CH 4 emission rates of entire oil and gas production regions in the United States [e.g., the Barnett shale, 76 metric tons per hour (18); the Haynesville shale, 80 metric tons per hour (19); the Fayetteville shale, 39 metric tons per hour (19); and the northeastern Marcellus shale, 15 metric tons per hour (19)].…”
Section: Supplementary Materialsmentioning
confidence: 76%
See 1 more Smart Citation
“…Further, at its peak, this leak rate exceeded that of the next largest point source in the United States-an underground coal mine in Alabama-by over a factor of 2 (14) and was a factor of 10 larger than the CH 4 leak rate reported from the Total Elgin rig blowout in the North Sea in 2012 (17). The Aliso Canyon CH 4 leak rates were comparable to the total CH 4 emission rates of entire oil and gas production regions in the United States [e.g., the Barnett shale, 76 metric tons per hour (18); the Haynesville shale, 80 metric tons per hour (19); the Fayetteville shale, 39 metric tons per hour (19); and the northeastern Marcellus shale, 15 metric tons per hour (19)].…”
Section: Supplementary Materialsmentioning
confidence: 76%
“…Biochemical studies confirmed that this abstraction in NosL is the first step in the conversion of L-tryptophan into MIA. NosL can perform b-scissions from the amino-centered radical intermediate at either Ca-Cb or Ca-C when using L-tryptophan analogs (17,18). These observations suggest a relative propensity of NosL for substrate promiscuity that, combined with slight differences in…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, the preparation of oxyhydrides is mainly required special synthesis conditions such as a solid state reaction at high-pressure [6][7][8] or a strong reducing reaction using metal hydrides as the reductant. [9][10][11][12][13] Although the synthesis of the LSLHO system by a conventional solid-state reaction at ambient pressure has been reported, it is only suitable for a standard composition of La 2 LiHO 3 , which contains the lowest concentration of H ¹ in this system. 14 ¹ and (LaSrO 2 ) + layers along the c-axis (Fig.…”
Section: ¹mentioning
confidence: 99%
“…59 Oxyhydride solid solutions (Ca,Sr)TiO 3¹x H x and (Sr,Ba)TiO 3¹x H x are prepared from corresponding ATiO 3 oxides. 61 Unlike the cobalt-based oxyhydride, BaTiO 3¹x H x has a common valence of Ti 3+/4+ , as seen in the Magnéli phases Ti n O 2n¹1 (n = integer), 64 and is electronically conducting. Furthermore, the hydride species is exchangeable with hydrogen gas at moderate temperatures.…”
Section: ç Transition Metal Oxyhydridesmentioning
confidence: 99%